TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) PT. KOTO ALAM SEJAHTERA DIBIDANG PERTAMBANGAN BATU TERHADAP LINGKUNGAN SEKITAR DAN MASYARAKAT KOTO ALAM KECAMATAN PANGKALAN KOTO BARU SUMATERA BARAT - Sutri Lasdienti; Firdaus Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Corporate social responsibility (CSR) is one of the obligations that must be carried out by companies in accordance with the contents of Article 74 paragraph (1) of the Limited Company Law (UUPT). CSR activities were originally a program that was voluntary or not required to be carried out by the company. This understanding changed when the government began to realize that CSR is very important to be implemented especially for companies engaged in mining or companies whose activities are related to natural resources. This is because mining companies are closely related to the environment. Many mining companies do not pay attention to the environment and surrounding communities so that the environment becomes damaged and the welfare of the community does not experience significant changes as they should.This study aims to determine the implementation of corporate social responsibility (corporate social responsibility) of PT. Koto Alam Sejahtera to the environment and the community of Koto Alam and to know the efforts that must be made by PT. Koto Alam Sejahtera in implementing CSR to create a good environment for the Koto Alam community. The type of research the writer uses is sociological research. In this sociological legal research, the authors obtain data through interviews with companies and the public and pay attention to supporting literature. The data obtained were then analyzed qualitatively and presented descriptively.The results of the CSR implementation research conducted by PT. Koto Alam Sejahtera is still not in accordance with the nature and ideals of CSR desired by the law because the implementation of CSR so far is only fulfilling the obligations required by the law. PT. Koto Alam Sejahtera also has not fulfilled the principles of propriety and reasonableness because the CSR program they are running is only giving money for community assistance, but there is no CSR program that aims to preserve the environment. so that the environment is not maintained, it will also affect the economy of the Koto Alam community.Keywords: corporate social responsibility - community – environment